2014
DOI: 10.1186/1745-6215-15-451
|View full text |Cite|
|
Sign up to set email alerts
|

CASPER plus (CollAborative care in Screen-Positive EldeRs with major depressive disorder): study protocol for a randomised controlled trial

Abstract: BackgroundDepression accounts for the greatest disease burden of all mental health disorders, contributes heavily to healthcare costs, and by 2020 is set to become the second largest cause of global disability. Although 10% to 16% of people aged 65 years and over are likely to experience depressive symptoms, the condition is under-diagnosed and often inadequately treated in primary care. Later-life depression is associated with chronic illness and disability, cognitive impairment and social isolation. With a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…Events characterized by declining health and disability, shown in this study to be the most prevalent in late life, may increase the risk of depression through reduced engagement in valued leisure activities, socializing and a decrease in the availability of emotional support (Blazer, 2003a). Studies in primary care are therefore trialling behavioural interventions for older adults with depression (Overend, Lewis, Bailey et al, 2014) to increase the amount of positive reinforcement they gain from functionally equivalent activities in which they are able to engage.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Events characterized by declining health and disability, shown in this study to be the most prevalent in late life, may increase the risk of depression through reduced engagement in valued leisure activities, socializing and a decrease in the availability of emotional support (Blazer, 2003a). Studies in primary care are therefore trialling behavioural interventions for older adults with depression (Overend, Lewis, Bailey et al, 2014) to increase the amount of positive reinforcement they gain from functionally equivalent activities in which they are able to engage.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Like other chronic health issues, depression management costs are an economic burden in health‐care systems worldwide . In addition, depression treatment costs may vary based on age.…”
Section: Discussionmentioning
confidence: 99%
“…Overend et al . reported that outpatient care costs were significantly greater and psychotherapy costs lower in patients older than 65 years compared to younger age groups . Expenditures on the management of mental health disorders among older patients, particularly for depression, has been shown to differ according to type of health care center.…”
Section: Discussionmentioning
confidence: 99%
“…In the CASPER plus (CollAborative care for Screen-Positive EldeRs with major depression) trial, [42][43][44] the BA intervention was acceptable for many of the older adults with depression and could readily be delivered over the telephone, following a face-to-face meeting. This approach may be able to reduce the stigma of the label of mental illness and resolve misconceptions around antidepressant medication prescribed by GPs.…”
Section: Figurementioning
confidence: 99%
“…The intervention was built on the literature, the research team's previous experience 39,42,76 and consensus achieved in an expert group.…”
Section: Refining the Interventionmentioning
confidence: 99%